Interface challenges in online processing: the role of crosslinguistic influence in L2 sentence comprehension - Sun Hee Park; Hyunwoo Kim (Language and Cognition)
The integration of multiple linguistic modules – syntax, semantics and pragmatics – poses a persistent challenge for adult second language (L2) learners, as posited by the interface hypothesis (IH). This study examines how crosslinguistic influence impacts L2 learners’ acquisition and processing of Korean quotative constructions at the syntax–semantics–pragmatics interface. Using offline acceptability judgment and online self-paced reading tasks, we compared Japanese- and Chinese-speaking learners of Korean. The results revealed that Japanese-speaking learners outperformed Chinese-speaking learners in offline tasks, demonstrating native-like sensitivity to case-marking constraints, likely due to the structural similarities between Japanese and Korean. However, neither learner group exhibited sensitivity to case-marking violations during real-time processing, unlike native Korean speakers. These findings suggest a dissociation between explicit knowledge and online processing abilities, supporting the IH and emphasizing the persistent challenges of integrating multiple linguistic domains in L2 processing. This study underscores the role of crosslinguistic influence in facilitating explicit knowledge acquisition while revealing its limitations in fostering native-like automaticity in online processing.